Intestinal preparations for colonoscopy. Comparative study: mannitol, picosulphate and macrogol - Quaresma,Abel Botelho (2018)
ABSTRACT Bowel preparation is mandatory prior to elective colonoscopy and their effectiveness is closely related to the quality of the examination. There are many preparations on the market and there is no consensus on which is best. This study aimed to compare three solutions for colon preparation in patients undergoing colonoscopy. We conducted a prospective study with 61 patients divided randomly into three groups: one that received a standard dose of macrogol, another received a standard dose of 10% mannitol and another received a standard dose of sodium picosulphate. Patients and examining endoscopists responded to questionnaires for compiling data. In the results we noticed that 10% mannitol, despite being less tolerated by the patient when compared to sodium picosulphate, presents better results in colonic cleaning, being therefore superior in this regard. Macrogol was considered as an intermediate in relation to the other two preparations. As for tolerability, preference is given to sodium picosulphate as best tolerated, followed by mannitol and by macrogol, which is poorly tolerated by the patient. We conclude that as the main objective of bowel preparation in colonoscopy is the quality of colonic cleaning, 10% mannitol was superior to the other preparations studied.